2016
DOI: 10.1155/2016/7565972
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Antibacterial Nanofibre/Nanoparticle Covered Composite Yarns

Abstract: The antibacterial efficiency of nanofibre composite yarns with an immobilized antibacterial agent was tested. This novel type of nanofibrous composite material combines the good mechanical properties of the core yarn with the high specific surface of the nanofibre shell to gain specific targeted qualities. The main advantages of nanofibre covered composite yarns over the standard planar nanofibre membranes include high tensile strength, a high production rate, and their ability to be processed by standard text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 19 publications
(23 reference statements)
0
27
0
Order By: Relevance
“…Electrospinning is a versatile technique for preparation of fine fibers down to a nanoscale size. An electrospun nanofiber provides high porosity, large surface area to volume ratio and good mechanical properties that can be used in various applications such as tissue engineering scaffold, filtration, and drug delivery system . In general, a needle electrospinning process consists of high voltage to create an electrical field between the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a versatile technique for preparation of fine fibers down to a nanoscale size. An electrospun nanofiber provides high porosity, large surface area to volume ratio and good mechanical properties that can be used in various applications such as tissue engineering scaffold, filtration, and drug delivery system . In general, a needle electrospinning process consists of high voltage to create an electrical field between the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CuO/nanofiber hybrid yarn showed a disinfection effect for both Gram‐negative E. coli and Gram‐positive S . gallinarum …”
Section: Introductionmentioning
confidence: 99%
“…The excellent properties of PVB make PVB nanofibers very attractive for researchers . In previous work, it was found that PVB/NP nanofibers are a promising candidate for antibacterial materials . Herein, we compared the antibacterial efficiency of various particles incorporated into PVB nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method still needs to optimize based on materials and the pattern of welding equipment. Other attempts to prevent damage of nanofiber webs have been done as nanofiber‐coated yarn . A macroscopic size random yarn has been used as core and nanofiber layer was covered around.…”
Section: Introductionmentioning
confidence: 99%